Predicting Life Satisfaction: Self-Efficacy and Cynical Attitudes - Bulut, Meryem Berrin (FSM Vakıf Üniversitesi, 2020)
This study aimed to investigate the effect of self-efficacy and cynical attitudes on life satisfaction. Participants, including 330 college students of whom 66.97% were women in the 18-36 age range (M = 21.20, SD = 1.91), from different academic departments and class levels of a state university in Middle Anatolia, completed the Self-Efficacy Scale, the Cynical Attitudes Towards University Scale, the Life Satisfaction Scale and the personal information form. In data analysis, correlation and regression analysis were utilized. The correlation analysis indicated significant relations between self-efficacy, cynical attitudes towards university, and life satisfaction. Self-efficacy and cynical attitudes towards university explained 17% of the variance in life satisfaction. The results were discussed in the light of information obtained from related literature and some suggestions for further studies were provided.

Bu çalışma, öz yeterlik ve sinik tutumların yaşam doyumu üzerindeki etkisini incelemeyi amaçlamaktadır. Çalışmaya katılan Orta Anadolu’daki bir devlet üniversitesinin farklı akademik bölüm ve sınıf seviyelerinden, 18-36 yaş aralığında (Ort. = 21.20, ss = 1.91), % 66.97’si kadın olan 330 üniversite öğrencisi Öz Yeterlik Ölçeği, Üniversiteye Yönelik Sinik Tutumlar Ölçeği, Yaşam Doyumu Ölçeği ve kişisel bilgi formunu doldurmuştur. Veri analizinde korelasyon ve regresyon analizi kullanılmıştır. Korelasyon analizi, öz-yeterlik, üniversiteye yönelik sinik tutumlar ve yaşam doyumu arasında anlamlı ilişkiler olduğunu göstermiştir. Öz yeterlik ve üniversiteye yönelik sinik tutumlar, yaşam doyumundaki varyansın % 17’sini açıklamıştır. Sonuçlar, ilgili literatürden elde edilen bilgiler ışığında tartışılmış ve ileride yapılacak çalışmalar için bazı öneriler sunulmuştur.
Yaşam Doyumunun Yordanması: Öz Yeterlik ve Sinik Tutumlar
Keywords: Satisfaction; Cynical Attitudes; Self-Efficacy; Students; Memnuniyet; Sinik Tutumlar; Öz Yeterlik; Öğrenciler